Paralingual Graphic Components in Modern English Written Discourse - Makaruk, Larysa (Lesya Ukrainka Eastern European National University, 2016)
The article is devoted to the study of paralinguistic graphic devices which are used in modern English-language written discourse. Identifying certain common elements of paralinguistic graphic means, it has been possible to place them in the following general groupings: segmentation and other graphic effects; font and color; non-pictorial and non-photographic graphic textual elements; iconic language elements (images); and other non-verbal means. Attention is devoted to the structure, semantics and pragmatics of certain elements that can be found in the groups mentioned above, and their specificity and distinctive features have been described. Several factors may account for this, the main one being the information revolution and the desire of producers and recipients to convey the maximum amount of information, doing so by using the smallest amount of semiotic resources, and those which have the most powerful pragmatic potential. Attention is given to the fact that paralinguistic written semiotic resources–stylistically distinctive coloured components–are capable of causing recipients to react in a different manner than they might have previously, or of influencing them in subtle ways which they themselves might not even perceive, to view the subject or the item which is under discussion in a somewhat different light than they might have otherwise done. The correlation of verbal and non-verbal components at different levels has been identified. Статтю присвячено паралінгвальним графічним компонентам комунікації, які функціонують у сучасному англійському писемному дискурсі. Виокремлені паралінгвальні компоненти поділено на кілька груп на основі виявлених спільних ознак. Серед них – сегментація тексту та інші графічні ефекти; шрифт та колір; непіктографічні та нефотографічні текстові елементи; іконічні мовні елементи (зображення); інші невербальні засоби. Звернуто увагу на структуру, семантику та прагматику окремих елементів, які є складниками означених груп. Обґрунтовано їх специфіку та диференційні ознаки. На основі ілюстративного матеріалу доведено, що використання невербальних компонентів невипадкове, а зумовлене низкою причин, провідними серед яких можна вважати інформаційну революцію та бажання реципієнтів й продуцентів передати та отримати максимум інформації, використовуючи при цьому мінімум семіотичних ресурсів з досить потужним прагматичним потенціалом. Звернуто увагу на те, що паралінгвальні писемні семіотичні ресурси – своєрідні стилістично забарвлені компоненти, здатні миттєво впливати на реципієнтів, змінювати їхню поведінку, спонукати до небажаних та не планованих заздалегідь дій. Окреслено кореляцію вербальних та невербальних компонентів на різних рівнях.
Keywords: paralingual components; semiotic resources; levels; correlation; verbal and nonverbal communication components; паралінгвальні компоненти; семіотичні ресурси; рівні; кореляція; модуси; вербальні та невербальні компоненти спілкування